2019
DOI: 10.1002/ppap.201900119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model for ultra‐precise surface machining of N‐BK7® using microwave‐driven reactive plasma jet machining

Abstract: In this paper, extensive studies are conducted as key to overcoming several challenging limitations in applying fluorine‐based reactive plasma jet machining (PJM) to surface machining of N‐BK7®, particularly regarding the manufacture of freeform optical elements. The chemical composition and lateral distributions of the residual layer are evaluated by X‐ray photoelectron spectroscopy and scanning electron microscopy/energy‐dispersive X‐ray spectroscopy analysis aiming at clarifying the exact chemical kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In other words, the surface temperature on a position x within the etched line is assumed to be constant. In the real experiment, the spatial temperature exhibits, however, a lateral distribution in the x, y plane that resembles a comet‐like footprint, as shown, for example, in the study reported by Kazemi et al [ 24 ] Thus, each position x experiences an increase of temperature up to the value taken in the model, and subsequently a decrease, when the plasma jet passes a certain position y . As the model disregards this temperature variation, the computed depth is larger than that observed in the experiment.…”
Section: Modeling Of Dynamic Etchingmentioning
confidence: 81%
See 2 more Smart Citations
“…In other words, the surface temperature on a position x within the etched line is assumed to be constant. In the real experiment, the spatial temperature exhibits, however, a lateral distribution in the x, y plane that resembles a comet‐like footprint, as shown, for example, in the study reported by Kazemi et al [ 24 ] Thus, each position x experiences an increase of temperature up to the value taken in the model, and subsequently a decrease, when the plasma jet passes a certain position y . As the model disregards this temperature variation, the computed depth is larger than that observed in the experiment.…”
Section: Modeling Of Dynamic Etchingmentioning
confidence: 81%
“…The plasma jet as a source of reactive species imposes a characteristic spatial distribution of fluorine flux on the surface, depending on the plasma parameters. Furthermore, according to our former investigation, [ 23,24 ] the heat flux of the plasma leads to the development of a spatio‐temporal surface temperature distribution. Both effects lead finally to the characteristic bell‐shaped profiles of the residual layer thickness or etching depth, which can be approximated by a Gaussian function as follows: D(r)=Dmax expr2σ2.…”
Section: Modeling Of Plasma Jet Etching Of N‐bk7 With Dg Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is a structural change of the residual layer from a densely closed layer occurring at room temperature to a porous layer found at elevated temperature. Thus, the fluorine atoms can penetrate the layer reaching the N-BK7 interface to proceed etching [2,3]. Although the absolute values of etching rate gradually decrease with increasing layer thickness, such a homogeneous behaviour is more suitable to be taken into account in a dwell-time based machining algorithm.…”
Section: Plasma Jet Machining Of N-bk7mentioning
confidence: 99%
“…It was shown that the excitation caused by APPJ can be induced by RF or microwave power. The interaction of APPJ with substrates have been experimentally [7][8][9] and theoretically [10] investigated. It has been demonstrated that APPJ processing can be used to etch a variety of different materials such as Si [11], technical glass [12], and SiC [13].…”
Section: Introductionmentioning
confidence: 99%